High‐throughput determination of Sudan Azo‐dyes within powdered chili pepper by paper spray mass spectrometry. (19th April 2013) - Taverna, Domenico; Di Donna, Leonardo; Mazzotti, Fabio; Policicchio, Barbara; Sindona, Giovanni
<x xml:space="preserve">Abstract</x> A high‐throughput mass spectrometric method is presented for the simultaneous detection of Sudan I, II, III, IV and Para‐Red azo‐dyes in foodstuff. The method is based on the use of paper spray mass spectrometry (MS) and deuterium‐labeled internal standards on a triple‐quadrupole instrument. A detailed assay of each azo‐dye was performed by the isotope dilution method, through the precursor ion scan approach, using deuterium‐labeled internal standards. The gas‐phase breakdown pattern of each labeled and unlabeled analogue displays the naphthoic moiety as a common fragment. Sudan dyes can be determined above the threshold of 1 ppm. Paper spray allows for a wide range of analytes and samples to be investigated by MS in the open air and without sample preparation and bypassing chromatography. Copyright © 2013 John Wiley & Sons, Ltd.